Constitutional Court Judges’ Constitutional Court Judges’ Interpretation Regarding the Limitation on the Presidential and Vice-Presidential Term of Office - Dewi Iriani; Muhammad Fauzan; Esti Ningrum (Universitas Muhammadiyah Surakarta, 2023)
ABSTRACT Purpose of the study: This paper aims to analyze the philosophical meaning of the Constitutional Court Judges' interpretation of Decision No. 117/PUU-XX/2022 on the limitation of presidential and vice-presidential terms of office. It also seeks to examine the limitations of the presidential and vice presidential terms of office in Indonesia's legal transformation and renewal. Methodology: This normative research used the qualitative method. The writers employed development law theory, judges’ interpretation, and philosophical theory. Results: It was revealed that the Constitutional Court Judges' interpretation of Decision No. 117/PUU-XX/2022 considered the grammatical, sociological, systematic, historical, comparative, and futuristic interpretations. The term limits for the president and vice president are part of Indonesia's legal reform and renewal efforts, which aim to establish a system of checks and balances among the state's highest institutions. The 1945 Constitution previously established this limitation. Applications of this study: Since presidential and vice-presidential candidates can only hold office for two terms, this research may motivate political parties to choose candidates who exhibit integrity, morals, and character. Finding the best persons to represent the nation is therefore preferable. Novelty/Originality of this study: There has not been any previous research that analyzes Constitutional Court Judges' interpretation of Decision No. 117/PUU-XX/2022 on the limitation of presidential and vice-presidential terms of office. The transformation and renewal of the law in Indonesia regarding term limits for the president and vice president should be guided by the applicable legal politics in Indonesia. Law No. 7 of 2017 concerning General Elections continues to be referenced in legal politics made by election organizers. The president's term of office is limited to two terms, according to Article 169 letter n and 227 letter i. Keywords: Judicial interpretation, constitutional court, term of office, president, Indonesia. ABSTRAK Tujuan Kajian: Tulisan ini bertujuan untuk menganalisis makna filosofis dibalik interpretasi hakim Mahkamah Konstitusi terhadap Putusan Nomor 117/PUU-XX/2022 tentang pembatasan masa jabatan presiden dan wakil presiden. Selain itu juga bertujuan untuk menganalisis pembatasan masa jabatan presiden dan wakil presiden dalam transformasi dan pembaharuan hukum di Indonesia. Metodologi: Penelitian ini merupakan penelitian normatif yang menggunakan metode kualitatif. Penulis menggunakan teori hukum pembangunan dan interpretasi hakim serta teori filosofis. Hasil Temuan Penelitian: Ditemukan bahwa interpretasi hakim konstitusi terhadap Putusan Nomor 117/PUU-XX/2022 mempertimbangkan interpretasi gramatikal, interpretasi sosiologis, interpretasi sistematis, interpretasi historis, interpretasi komparatif, dan interpretasi futuristik. Dalam transformasi dan pembaharuan hukum di Indonesia, pembatasan masa jabatan presiden dan wakil presiden bertujuan untuk menciptakan sistem check and balances antar lembaga tinggi negara. Pembatasan ini sudah sesuai dengan UUD 1945. Aplikasi Studi: Penelitian ini dapat memotivasi partai politik untuk menjadi calon presiden dan wakil presiden yang memiliki integritas, moral, dan akhlak, karena presiden dan wakil presiden hanya dapat menjabat selama dua periode. Jadi, yang terbaik adalah menemukan kandidat terbaik untuk mengabdi pada negara. Kebaruan/Originalitas penelitian: Belum ada penelitian sebelumnya yang menganalisis interpretasi hakim Mahkamah Konstitusi terhadap Putusan Nomor 117/PUU-XX/2022 tentang pembatasan masa jabatan presiden dan wakil presiden. Tranformasi dan pembaharuan hukum di Indonesia terhadap Pembatasan masa jabatan Presiden dan Wakil Presiden. Hendaknya berperdoman pada politik hukum yang berlaku di Indonesia, politik hukum berupa pembuatan kebijakan dari penyelenggara pemilu tetap mengacu pada Undang No 7 Tahun 2017 tentang Pemilihan Umum. Pasal 169 huruf n, dan Pasal 227 huruf I yang mempertahankan masa jabatan Presiden hanya berlaku dua kali masa jabatan. Kata kunci: Penafsiran yudisial, mahkamah konstitusi, masa jabatan, Presiden, Indonesia